Antimicrobial strategies for scaffolds aided periodontal regeneration- road so far systematic review - Farwa Rais; Hashmat Gul; Zainab Qasim; Amna Zaheer; Muhammad Kaleem (Journal of the Pakistan Medical Association, 2022)
Objective: To give a comprehensive understanding of the efficacy of antimicrobial-loaded scaffolds as drug delivery system for periodontal regeneration, and to review the recent advances in the field of periodontal regeneration. Methods: The literature was reviewed using key words “antimicrobial releasing periodontal scaffolds” on Science Direct, PubMed and Web of Science search engines. Shortlisted articles were evaluated on the basis of specific inclusion-exclusion criteria. Results: Of the 544 studies found, 34(6.25%) met the inclusion criteria. The trend indicated an increase in use of antimicrobial-loaded scaffolds that caused inhibition of periodontal pathogenic bacteria, accompanied with greater cellular interaction, and differentiation for alveolar bone healing. Contemporary treatment tactics clinically prove the ability to limit disease progression, but complete periodontal regeneration needs to be validated yet. Conclusion: Emerging trends are not only improving the inhibitory effect of bacterial growth, but are also making a favourable environment for cell proliferation and differentiation, resulting in alveolar bone repair and re-growth. Key Words: Periodontal scaffolds, Antimicrobials, Alveolar bone regeneration.